Work performance incentivization in the Philippine public educational organization - Jamoral, Rockangel; Batag, Mark James; Andres, Kayvett Azryll (Journal of Management, Economics, and Industrial Organization, 2023)
This study investigates the impact of Performance-Based Bonus (PBB) in incentivizing the work performance of public-school teachers in the Philippine educational bureaucracy. Using a cross-sectional design, a survey was administered to public school teachers and personnel in 10 selected schools in the Cagayan Valley region, Philippines. The mechanism of incentivizing work performance is found efficient in increasing work productivity. The interplay of top-down and bottom-up management approaches is paramount in the planning and realization of the agency’s PBB key result areas. However, there are perceived issues that the PBB scheme needs further clarification and improvement in its implementation. Regardless of how they may feel about the practical difficulties in the PBB implementation, it serves its purpose as a strong incentivizing scheme for employees to perform, which has a good effect on work productivity.